Dialogic literary gatherings from the point of view of teachers and children’s families in early childhood education (Revista Contexto & Educação, 2026)
In this paper we report on the initial results of a broader research project obtained from a communication group with teachers and an interview with children and their families. The aim is identify transformative and exclusionary elements in a Successful Educational Actions (SEA) - Dialogic Literary Gathering (DLG) and its impact on children's learning. Theoretically, it discusses SEAs, their basis in Dialogic Learning and their relevance to Early Childhood Education. The principles and techniques of the Communicative Research Methodology were used and, as a result, 4 categories were developed to highlight the impact of the experiences in the DLG: (1) Children's preparation for the DLG; (2) Children's participation in the DLG; (3) Quality of the interactions prompted by the DLG and (4) Instrumental learning through the DLG. The implementation of DLG in the investigated school indicates a positive impact on children's learning and development and, as the other SEA are implemented, this impact will be strengthened both in terms of learning and improving coexistence in the school.
Keywords: literacy for young children; egalitarian dialogue; social impact